Integration of the Herbst and Begg appliance in the management of severe Class II malocclusion - Asavari L Desai; Manjunath Hegde; M R Dinesh; B C Amarnath (Wolters Kluwer Medknow Publications, 2014)
The efficacy of the Herbst appliance in a normalizing sagittal relationship in patients with a Class II malocclusion is well-documented. This case report describes the treatment of a 14-year-old male patient with severe Class II Division 1 malocclusion due to retrognathic mandible and mildly prognathic maxilla, convex profile, and lip trap. He had severely proclined maxillary incisors and retroclined mandibular incisors, overjet of 13 mm and overbite of 7 mm. Since the patient was in the peak pubertal growth phase, growth modulation was carried out with the Herbst appliance for 8 months, followed by fixed appliance therapy with the Begg appliance for 11 months. Combination of Herbst and Begg appliance led to a very favorable treatment outcome and greatly improved the patient's appearance.